Comparison of Microbiomes between Red Poultry Mite Populations (Dermanyssus gallinae): Predominance of Bartonella-like Bacteria - Hubert, Jan; Erban, Tomas; Kopecky, Jan; Sopko, Bruno; Nesvorna, Marta; Lichovnikova, Martina; Schicht, Sabine; Strube, Christina; Sparagano, Olivier (Microbial ecology, 2017)
Blood feeding red poultry mites (RPM) serve as vectors of pathogenic bacteria and viruses among vertebrate hosts including wild birds, poultry hens, mammals, and humans. The microbiome of RPM has not yet been studied by high-throughput sequencing. RPM eggs, larvae, and engorged adult/nymph samples obtained in four poultry houses in Czechia were used for microbiome analyses by Illumina amplicon sequencing of the 16S ribosomal RNA (rRNA) gene V4 region. A laboratory RPM population was used as positive control for transcriptome analysis by pyrosequencing with identification of sequences originating from bacteria. The samples of engorged adult/nymph stages had 100-fold more copies of 16S rRNA gene copies than the samples of eggs and larvae. The microbiome composition showed differences among the four poultry houses and among observed developmental stadia. In the adults' microbiome 10 OTUs comprised 90 to 99% of all sequences. Bartonella-like bacteria covered between 30 and 70% of sequences in RPM microbiome and 25% bacterial sequences in transcriptome. The phylogenetic analyses of 16S rRNA gene sequences revealed two distinct groups of Bartonella-like bacteria forming sister groups: (i) symbionts of ants; (ii) Bartonella genus. Cardinium, Wolbachia, and Rickettsiella sp. were found in the microbiomes of all tested stadia, while Spiroplasma eriocheiris and Wolbachia were identified in the laboratory RPM transcriptome. The microbiomes from eggs, larvae, and engorged adults/nymphs differed. Bartonella-like symbionts were found in all stadia and sampling sites. Bartonella-like bacteria was the most diversified group within the RPM microbiome. The presence of identified putative pathogenic bacteria is relevant with respect to human and animal health issues while the identification of symbiontic bacteria can lead to new control methods targeting them to destabilize the arthropod host.
Keywords: roztoči; taxonomické DNA čárové kódování; Transmission; DNA Barcoding, Taxonomic; druhová specificita; mikrobiota; Tsukamurella; Mites; RNA ribozomální 16S; bakteriální RNA; Microbiota; Blood sucking; zvířata; Ricketsiella; RNA, Ribosomal, 16S; Poultry; Wolbachia; Bartonella; Czech Republic; Species Specificity; Mite; Bacteria; Animals; Česká republika; RNA, Bacterial